2021
DOI: 10.1155/2021/8554829
|View full text |Cite
|
Sign up to set email alerts
|

Use of Traditional Chinese Medicine and Its Impact on Medical Cost among Urban Ischemic Stroke Inpatients in China: A National Cross-Sectional Study

Abstract: Background. Traditional Chinese medicine (TCM) has long been widely adopted by the Chinese people and has been covered by China’s basic medical insurance schemes to treat ischemic stroke. Previous research has mainly highlighted the therapy effect of TCM on ischemic stroke patients. Some studies have demonstrated that employing TCM can reduce the medical burden on other diseases. But no research has explored whether using TCM could reduce inpatient medical cost for ischemic stroke in mainland China. The purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…However, our study using medical insurance data for lung cancer in mainland China did not find similar findings. We found that the total inpatient cost of TCM users was higher than those of TCM nonusers controlling for demographic characteristics, a finding consistent with the study by Huang et al for ischemic stroke [ 23 ]. This seems to be contrary to previous research that demonstrated CAM was generally cheaper than conventional medication, and that the use of CAM could reduce the economic burden of disease [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, our study using medical insurance data for lung cancer in mainland China did not find similar findings. We found that the total inpatient cost of TCM users was higher than those of TCM nonusers controlling for demographic characteristics, a finding consistent with the study by Huang et al for ischemic stroke [ 23 ]. This seems to be contrary to previous research that demonstrated CAM was generally cheaper than conventional medication, and that the use of CAM could reduce the economic burden of disease [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the results of previous studies. Huang et al concluded that medical costs for hospitalized TCM users were 32.5% higher than for TCM nonusers, and that the cost of TCM increased significantly with increasing prescriptions of conventional medicine, which suggesting that TCM treatments were complements, rather than substitutes, to conventional treatment [ 22 ]. Nie et al concluded that medication costs, conventional medication costs and nonpharmacy costs for TCM users were higher than for TCM nonusers, revealing that the higher medical costs for TCM users were not just to do with TCM treatments [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liao et al, using Taiwan’s 2005 Longitudinal Health Insurance Database, found that the TCM insurance cost was consistently lower than those covering biomedicine in patients with liver cancer [ 17 ]. Huang et al concluded that TCM mainly played a complementary role to conventional medicine in the treatment of Chinese mainland ischemic stroke [ 22 ]. The above researches demonstrated the influence of TCM using either on treatment effect or on the economic burdens of other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship and underlying mechanism between the risk factors and inpatient costs of stroke have not been given attention in the last 10 years [ 11 ]. Most current studies have focused on the prevalence and disease burden of stroke and its attributing risk factors [ 12 ]. Therefore, this study aimed to explore the relationship between risk factors and stroke-related inpatient costs.…”
Section: Introductionmentioning
confidence: 99%